Stakeholders’ preferences for land assembly: Development with rural urban synergy - KALSI, NAMRITA; KIRAN, RAVI (The Indian Journal of Agricultural Sciences, 2015)
Sensitized and consultative approach is critical to defuse agrarian crisis in India. Unified development strategy of urban-rural continuum can be a natural outcome to discover a collectively acceptable model to key stakeholder. In the postulated model, the precincts of land owner, agriculturist, developer, Government or buyer are seen to be melting away. “Framework for acceptable land assembly” is critical for development of city regions, which is undeniably an uphill task, worldwide today. Urbanization is an engine of growth for which Regional and Master Plan is an important tool for development. Yet land-owners resistance has power to stall even a well conceptualized, sustainable, practical, statutorily compliant, technically sound, and financially viable “Master Plan”. The consequence is that the landowner or agriculturist feels alienated in the development process resulting in agrarian crisis and possible rural-urban divergence. Exploring this trend further a questionnaire as primary research tool was administered to stakeholders- landowners, Developers or Government and End User from India, a third world country to identify preferential mode(s) of land assembly. The study tries to converge and extract the most appropriate method and infers that land assembly has got fused with development process. In the end the paper brings out innovative implementation model suitable to all stakeholders as a feasible way onward. The paper tries to highlight the research gap for establishing judicious allocation of land for rural-urban synergy and tries to find an answer whether going vertical for both is possible?